Connecting performance evaluation of the Quick-Connector for modular steel construction - Lee, Doo Yong; Cho, Bong Ho; Jung, Dam I.; Choi, Joon Young; Lee, Jae Sub; Cho, Kyung Hwan; Park, Jong Kun; Shin, Myoung Gyu (Engineering Structures, 2024)
This study presents the Quick-Connector, a new self-fastening joint system designed specifically for modular steel construction. By eliminating the need for a dedicated workspace during the connection process, the Quick-Connector minimizes disruptions to finishing work. A comprehensive set of tests, including pull-out, shear, and cyclic tests, was conducted on a full-scale prototype to evaluate its structural performance. The experimental results demonstrate that the Quick-Connector exhibits exceptional connecting performance, meeting the shear and tensile strength requirements for high-tension bolts. The seismic performance of the Quick-Connector was also evaluated through cyclic testing, highlighting its potential as a viable replacement for high-tensile bolts. Furthermore, a push-over analysis was carried out to develop an elastic structural design model specifically for buildings incorporating the Quick-Connector. The analysis results closely aligned with the experimental findings, validating the accuracy of the proposed model. Overall, the Quick-Connector offers a promising alternative to traditional bolted connections in modular construction, with the potential to enhance construction efficiency, quality, and safety.
Keywords: Finishing works; Joint system; Minimize disruption; Modular steel construction; Modulars; Performances evaluation; Push-over analysis; Quick-connector; Seismic Performance; Structural performance; Modular steel construction; Push-over analysis; Quick-connector; Seismic performance; Structural performance